2013
DOI: 10.1016/j.jaci.2012.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Obesity impairs apoptotic cell clearance in asthma

Abstract: Background Asthma in obese adults is typically more severe and less responsive to glucocorticoids than asthma in nonobese adults. Objective We sought to determine whether the clearance of apoptotic inflammatory cells (efferocytosis) by airway macrophages was associated with altered inflammation and reduced glucocorticoid sensitivity in obese asthmatic patients. Methods We investigated the relationship of efferocytosis by airway (induced sputum) macrophages and blood monocytes to markers of monocyte program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 71 publications
0
48
0
Order By: Relevance
“…A large number of cross-sectional and longitudinal studies have reported worse asthma control and increased asthma severity in obese individuals. The significantly higher percentage of macrophages that we observed in the induced sputum of obese children, along with their altered phenotype [36] and activity [37], highlight the potential implication of airway macrophages on clinical aspects of obese asthma. Furthermore, the enhanced reactivity of alveolar macrophages from overweight/obese adult asthmatics to lipopolysaccharide, particularly when they were primed ex vivo with high dose of leptin, was demonstrated in an elegant study by LUGOGO et al [36].…”
Section: Discussionmentioning
confidence: 53%
“…A large number of cross-sectional and longitudinal studies have reported worse asthma control and increased asthma severity in obese individuals. The significantly higher percentage of macrophages that we observed in the induced sputum of obese children, along with their altered phenotype [36] and activity [37], highlight the potential implication of airway macrophages on clinical aspects of obese asthma. Furthermore, the enhanced reactivity of alveolar macrophages from overweight/obese adult asthmatics to lipopolysaccharide, particularly when they were primed ex vivo with high dose of leptin, was demonstrated in an elegant study by LUGOGO et al [36].…”
Section: Discussionmentioning
confidence: 53%
“…Patrolling monocytes, increased among obese subjects with asthma and associated with disease severity in our study, are rapidly recruited into lungs in response to inflammatory stimuli (22) and are potent producers of TNF (23), a cytokine that was higher among obese subjects with asthma than normal-weight subjects with asthma in our study. Furthermore, airway macrophages are derived from circulating patrolling monocytes (22), and are known to be proinflammatory in response to leptin (24) and have reduced efferocytosis in obese subjects with asthma compared with normal-weight subjects with asthma (25).…”
Section: Discussionmentioning
confidence: 99%
“…Log-transformed data are presented as geometric mean (95% confidence interval). Sputum cytokine concentrations and eosinophilic inflammation in different compartments were presented in the subjects with asthma stratified by BMI (, 25 …”
Section: Discussionmentioning
confidence: 99%
“…The association of obesity and asthma has been evident from epidemiologic studies, including case control studies and crosssectional studies that have shown an increased risk of asthma in obese individuals based on the body mass index (BMI) (20)(21)(22)(23). Emerging evidence suggests that obesity might represent a distinct severe asthma phenotype (6) with changes in exhaled nitric oxide metabolism (24) and macrophage function (25,26). Its association with eosinophilic inflammation is contentious with some reports suggesting no association with sputum (27) or blood cell counts (6) and others suggesting there is a noneosinophilic obese phenotype (7).…”
mentioning
confidence: 99%